DOZ047.41: Tracheomalacia after esophageal repair: a systematic review. (24th June 2019) - Aanen, I P; Elders, B B L J; Pullens, B; Wijnen, R M H
Abstract: : This study was performed to obtain an overview of literature on diagnosing tracheomalacia (TM) in patients with esophageal atresia (EA). The aim of this study is to find answers in the literature on the following questions: (1) How often is a TM seen on preoperative scopy? (2) What is the predictive value of preoperative scopy findings on postoperative TM outcome? (3) How often is tracheomalacia seen in postoperative scopy in EA? (4) How often is tracheomalacia severe? Methods: A systematic literature search to identify studies on pre-, per-, and postoperative endoscopy to identify TM in patients with EA was performed. TM was classified into the following categories: mild, moderate, and severe, based on percentage of collapse of the trachea seen on tracheobronchoscopy (TBS) and/or clinical symptoms. The following databases were searched: Embase, Medline Epub (Ovid), Cochrane Central, Web of Science, Google Scholar. The search strategy contained 'oesophageal atresia' and 'tracheo-oesophageal fistula' and 'tracheomalacia' and 'pediatric.' Main Results: A total of 43 articles were included. Of the studies who conducted initial TBS pre- or peroperative, 6 described TM incidences, ranging from 7% to 65%. One study reported a sensitivity of dynamic fiberoptic bronchoscopy at time of initial repair as a test for symptomatic TM of 86% and a specificity of 54%. The positive and negative predictive values were 71% and 75%, respectively. Thirty-three studies described postoperative TM incidences ranging from 0% to 89% overall. Of the patients who were identified with TM 8–53% were classified as severe, e.g., in need of surgical intervention or according to institute guidelines on collapse percentage at endoscopy. Conclusions: Although most medical centers carry out airway endoscopy pre- or peroperative in EA-repair patients, reports on TM incidences at this time point are still poor. Postoperative TM occurs highly in symptomatic patients with a substantial number of airway interventions.